2014
DOI: 10.1371/journal.pone.0093671
|View full text |Cite
|
Sign up to set email alerts
|

The Association between the History of Cardiovascular Diseases and Chronic Low Back Pain in South Koreans: A Cross-Sectional Study

Abstract: BackgroundCardiovascular disease and related risk factors have been suggested as a mechanism leading to atherosclerosis of the lumbar vessels and consequent lumbar pain or sciatica. But there is continued controversy concerning its generalization. This study examined whether cardiovascular disease or its risk factors were associated with chronic low back pain (cLBP) in Koreans.MethodsHealth surveys and examinations were conducted on a nationally representative sample (n = 23,632) of Koreans. A total of 13,841 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 38 publications
2
26
0
1
Order By: Relevance
“…This study was based on a large, representative Korean population with data obtained from a well-established national cohort [38]. The prevalence of LBP in this study was comparable with previous studies [6][7][8][9]45]. Risk prediction equations based on general medical practice data are easily implemented in medical practice [46], and we believe our results are applicable to the general Korean popula-Mukasa and Sung tion.…”
Section: Discussionsupporting
confidence: 80%
“…This study was based on a large, representative Korean population with data obtained from a well-established national cohort [38]. The prevalence of LBP in this study was comparable with previous studies [6][7][8][9]45]. Risk prediction equations based on general medical practice data are easily implemented in medical practice [46], and we believe our results are applicable to the general Korean popula-Mukasa and Sung tion.…”
Section: Discussionsupporting
confidence: 80%
“…No definite associations were found between back pain and lipid levels in other cross-sectional studies [10]–[12], [15], but in many cases results were not adjusted for other risk factors. However, in a Finnish study [37] associations were observed in men between prevalence of sciatica and levels of total and low density lipoprotein (LDL) cholesterol and triglycerides but not HDL cholesterol, in analyses adjusted for BMI and other confounders.…”
Section: Discussionmentioning
confidence: 75%
“…Only few studies [8][15] have dealt with associations between LBP and abnormal serum lipid levels, representing established risk factors for atherosclerosis [16]. In particular, large prospective studies of potential relationships between lipid levels and risk of LBP are needed.…”
Section: Introductionmentioning
confidence: 99%
“…Individual respondents' understanding of and political attitude towards the term influences response. Debate on the elusive nature of a plausible inert placebo for use in clinical trials of acupuncture is not new [48]. Superficial needling or the application of non-penetrative devices to acupuncture points is recognised to stimulate these points in a manner equitable to a lower dose of the same treatment [49,50] and subsequent research in this area has led to the development of pragmatic trial models which assess the effectiveness of acupuncture treatment against active comparators in ecologically valid settings [51,52].…”
Section: Interpretive Analysismentioning
confidence: 99%
“…Other causes associated with an increased risk of LBP, include infections, autoimmune diseases, orthopedic diseases or tumours [27][28][29][30][31][32][33]. LBP results also from occupational ergonomic factors related to heavy physical work, repetitive actions due to occupational requirements [1,2,[34][35][36][37][38][39]; as well as sports activities or sports-related injuries [40,41]; sedentary lifestyle, prolonged sitting or inactivity and lack of exercises [42][43][44]; post operation or surgery-induced [45,46]; secondary from other medical conditions [47][48][49]; lifestyle factors [50]; poor trunk control and postural impairment [51]; psychosocial and behavior-related factors from smoking, alcohol abuse, obesity, depression and stress [1,6,14,[52][53][54][55][56][57]; socio-economic factors [58]; and ageing [59,60]. However, it is often difficult to identify the origin of LBP [1,5,6,[61][62][63][64][65] and 85-95% of the total cases of back...…”
Section: Causes and Risk Factors Of Lower Back Painmentioning
confidence: 99%